E-learning Today. - A.M. Josceanu; A.M. Dumitrescu; T.D. Danciu; R.D. Isopescu; P. Postelnicescu; V. Plesu; C. Stefan (Chemical Engineering Transactions, 2010)
Abstract preview not available - see full-text PDF article.